Fourier transform infrared analysis of orange peel ferroelectric material with BaTiO3 precursor - Rahmi Dewi; Yanuar Hamzah; Romarito Gesi Manurung; Ropina Emwarjati Sihombing; Lailatul Rahmi; Rahmatan Lil Alamin; Figo Swarna Yoga; Sonia Salsabila; Ananda Febri Yudani (Science, Technology, and Communication Journal, 2024)
This study explores the potential of orange peel extract as a stabilizing agent in the synthesis of ferroelectric BaTiO3. Characterization using Fourier transform infrared (FTIR) spectroscopy revealed the presence of strong acidic functional groups (O-H stretching at 3300 cm-1 and C–H sp3 chain at 2800 – 2993 cm-1 and carbonyl groups of double C–O at 1650 cm-1 in orange peel extract. These findings indicate that orange peel contains organic compounds that can be utilized in various applications.